Pengaruh Kompensasi Terhadap Kinerja Karyawan Pada Perusahaan Warunk Bendito Manado - Nirvana M. Sangkaen; Wehelmina Rumawas; Sandra Asaloei (Universitas Sam Ratulangi, 2019)
This study aims to determine the effect of compensation on employee performance. With the problem of compensation for the performance of employees at the Warunk Bendito Manado company. The sample taken was 34 people from a total of 34 employees in the company. In this study used a type of quantitative research. Technique data collection uses questionnaires to respondents, making observations and interviews. The technique used in data analysis is to use simple regression statistics with SPSS version 22.00 to test the significance of the relationship between variables and to measure the magnitude of the effect that occurs on compensation variables and employee performance variables. From the results of t test and correlation, it can be seen that the results of tvalue < ttable have a negative influence. The results of the R square correlation value have a weak correlation. Based on the results of calculations from the study it can be seen that the compensation variable has a negative effect on employee performance variables.